Fighting terrorism in the liberal state : an integrated model of research, intelligence and international law - Peleg, Samuel; Kempf, Wilhelm F. (NATO security through science series. Human and societal dynamics, 2006)
Contains papers that illustrate the balanced dichotomy between terrorism and counter-terrorism against the background of the liberal state. How to establish the equilibrium of combating terrorism while preserving the liberties of the open society? This book begins with this question and tackles different aspects and dimensions of this dilemma.